Quasi Duo Rings whose Every Simple Singular Modules is YJ-Injective - Mohammed, Akram; AL-Salihi, Sinan (Iraqi Journal of Science, 2023)
In this paper , we give some characterizations and properties of Quasi duo rings whose every simple singular module is YJ-injective . and we study the relation between this rings and other rings , like NI-ring, non singular rings, generalized -regular ring, strongly regular and n-regular ring .